Oxygen limitation and thermal tolerance: a comparison of pulmonate and patellogastropod limpets - Kankondi, Sebbi (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
Since the scientific community anticipates a general change in the global climate, it has become increasingly important to develop predictive models which encompass mechanisms to generate reliable forecasts of the effects this change on ecological communities and processes. To this end, the oxygen- and capacity- limited thermal tolerance (OCLTT) theory has been developed as a link between various physiological processes, the thermal aspect of climate change and the associated shifts at different levels of biological organization. This study set out to assess the general applicability of the OCLTT theory in eurythermal pulmonate and patellogastropod limpets, whose distributions overlap on the high shore rocks of the warm temperate, south-east coast of South Africa.This was done by determining their microhabitat use, median lethal temperatures and cardiac, Arrhenius breakpoint temperatures as measures of their upper thermal tolerance limits, in both air and water. The main hypotheses of the study were that the pulmonate limpets would be more common than the patellogastropods in warmer microhabitats during low tide and would have higher thermal limits than the patellogastropods in air and vice versa in water. This was based on the assumption that the two limpet groups have different capabilities of oxygen consumption in air and water, due to differences in their respiratory organs and that this would be reflected in their thermal tolerances based on predictions made by the OCLTT. This assumption was important because oxygen consumption was not measured in this study. Previous research (e.g. Garrity, 1984), showed that a thermal stress gradient exists among rocky intertidal microhabitats. From most to least thermally stressful the gradient is horizontal surfaces> slopes> vertical surfaces> tide pools> crevices. The current study found that, while the pulmonate limpets, Siphonaria capensis and S. serrata, preferred rock pools, sloped, vertical and horizontal rock surfaces, the patellogastropod limpets, Cellana capensis and Scutellastra granularis, preferred rock pools and vertical rock surfaces. Furthermore, the pulmonate limpets were only common on horizontal rock surfaces where specific ameliorating conditions would have mitigated thermal stress there. In addition, C. capensis had similar thermal tolerance limits to the pulmonate limpets in air and the pulmonate limpets had similar and/or higher thermal tolerance limits compared to S. granularis in water. This indicates that the pulmonate limpets did not necessarily prefer warmer microhabitats than the patellogastropod limpets and that there were no differences in the collective upper thermal tolerance limits between the two limpet groups in either medium.Consequently, there was no indication from this study that an assumed superior capacity for oxygen supply translates into greater thermal tolerance and that the hypotheses based on the OCLTT were not supported. Although this was an indirect test of the OCLTT theory, I conclude that this study does not support the notion of its general applicability and that mechanisms other than those outlined by the OCLTT theory may help explain the patterns of thermal limitation observed in the current study.
Keywords: Thermal tolerance (Physiology); Limpets -- Physiology; Limpets -- Effect of temperature on; Oxygen consumption (Physiology)